Fortificação com micronutrientes em creche reduz anemia em crianças - Pereira, Thais Cristina da Costa Rocha (2017)
Introduction: Iron deficiency anemia is the leading cause of childhood anemia. The consequences of this clinical condition affect even developed countries. Food fortification has been very relevant, promoting the best cost -benefit ratio in terms of treatment. Objective: To evaluate the efficacy of NutriSUS micronutrient fortification in children aged 12 to 36 months for prophylaxis and treatment of iron deficiency anemia. Methods: A randomized clinical trial was carried out in a municipal nursery, located in the urban perimeter of the municipa lity of Sobral, Ceará, in northeastern Brazil. A total of 130 children were studied per 12-week period. The children were allocated into two groups by means of room randomization: NutriSUS micronutrient fortification (Group A) and control (Group B). The primary outcome variables were changes in hemoglobin concentration and in the prevalence of anemia. Two biochemical evaluations were performed to determine hemoglobin concentrations before and after the intervention. Results: For group A, the hemoglobin concentration was 11.4 ± 1.01 g / dL at baseline and 11.9 ± 0.90 g / dL after the intervention, p = 0.006; 15 of the 20 participants who were anemic at the start of the study had normal Hb levels after the intervention. Number needed to treat (NNT) = 2. In group B, mean baseline hemoglobin was 11.9 ± 0.89 g / dL at the baseline baseline, and 12.2 ± 0.92 g / dL after the intervention , P = 0.58; 4 of the 5 participants with anemia at baseline remained anemic after the intervention. Conclusions: In our study, NutriSUS micronutrient fortification provided a beneficial effect on Hb values, reducing the prevalence of anemia. However, additional studies are needed to confirm the efficacy of this intervention in populations on a larger scale.